Management delayed tooth injury fixed with orthodontic splint system: A case report - Meidiana Adiningsih; Mohammed Ahmed Aljunaid; Prawati Nuraini (Indonesian Journal of Dental Medicine, 2026)
Background: Dentoalveolar trauma, specifically luxation injuries, is a common occurrence in mixed dentition, with an incidence ranging from 18% to 33%. This condition can severely impact the periodontal ligament and the vitality of the affected teeth. Maxillary anterior teeth are most frequently affected due to their prominent position in the dental arch. Appropriate intervention is crucial to preserve both function and aesthetic. Purpose: Reported a case management of upper front right teeth lateral luxation with fixed orthodontic to ensure proper healing and functionality. Case: A 14-year-old female patient presented to a pediatric dental clinic with complaints of pain and displacement of her right upper front tooth, which had been pushed-back following a physical altercation with peers one-week prior. The patient was currently managing her pain with analgesic, the last dose taken that morning. Her mother was worried about the tooth’s return to it’s normal position. Case Management: After confirming complete root formation and absence of alveolar fracture via panoramic radiograph, the tooth was initially stabilized using fixed orthodontic appliances with NiTi wire (0.016” x 0.016”) to encourage gradual repositioning. Oral prophylaxis was performed prior to bracket placement, and the patient was advised on maintaining oral hygiene and a soft diet with follow-up planned for malocclusion correction and pulp vitality assessment. Conclusion: It should be taken into consideration to use fixed orthodontics to reposition and splint delayed traumatized teeth.